Effects of glycyrrhiza polysaccharides on growth performance, meat quality, serum parameters and growth/meat quality-related gene expression in broilers - Li, Tiyu; Qin, Weize; Wu, Baiyila; Jin, Xiao; Zhang, Rui; Zhang, Jingyi; Du, Liyin (Frontiers in Veterinary Science, 2024)
With growing restrictions on the use of antibiotics in animal feed, plant extracts are increasingly favored as natural feed additive sources. Glycyrrhiza polysaccharide (GP), known for its multifaceted biological benefits including growth promotion, immune enhancement, and antioxidative properties, has been the focus of recent studies. Yet, the effects and mechanisms of GP on broiler growth and meat quality remain to be fully elucidated. This study aimed to investigate the effects of GP on growth, serum biochemistry, meat quality, and gene expression in broilers. The broilers were divided into five groups, each consisting of five replicates with six birds. These groups were supplemented with 0, 500, 1,000, 1,500, and 2,000 mg/kg of GP in their basal diets, respectively, for a period of 42 days. The results indicated that from day 22 to day 42, and throughout the entire experimental period from day 1 to day 42, the groups receiving 1,000 and 1,500 mg/kg of GP showed a significant reduction in the feed-to-gain ratio (F: G) compared to the control group. On day 42, an increase in serum growth hormone (GH) levels was shown in groups supplemented with 1,000 mg/kg GP or higher, along with a significant linear increase in insulin-like growth factor-1 (IGF-1) concentration. Additionally, significant upregulation of GH and IGF-1 mRNA expression levels was noted in the 1,000 and 1,500 mg/kg GP groups. Furthermore, GP significantly elevated serum concentrations of alkaline phosphatase (AKP) and globulin (GLB) while reducing blood urea nitrogen (BUN) levels. In terms of meat quality, the 1,500 and 2,000 mg/kg GP groups significantly increased fiber density in pectoral muscles and reduced thiobarbituric acid (TBA) content. GP also significantly decreased cooking loss rate in both pectoral and leg muscles and the drip loss rate in leg muscles. It increased levels of linoleic acid and oleic acid, while decreasing concentrations of stearic acid, myristic acid, and docosahexaenoic acid. Finally, the study demonstrated that the 1,500 mg/kg GP group significantly enhanced the expression of myogenin (MyoG) and myogenic differentiation (MyoD) mRNA in leg muscles. Overall, the study determined that the optimal dosage of GP in broiler feed is 1500 mg/kg.